2018
DOI: 10.1111/jgs.15381
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Phenotype and Healthcare Costs and Utilization in Older Women

Abstract: Intermediate stage and frail older community-dwelling women had higher subsequent total healthcare costs and utilization after accounting for multimorbidity and functional limitations. Frailty phenotype assessment may improve identification of older adults likely to require costly, extensive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 38 publications
4
106
2
Order By: Relevance
“…56 Multiple studies using cohorts of community-dwelling older adults have showed that the health care costs of frail individuals are sometimes several-fold higher than those of non-frail counterparts. [57][58][59][60][61] Older adults form the main users of medical and social care services, 62 and the majority of health care costs are incurred by them. In the context of ongoing population aging, with an unprecedented growing number and proportion of older adults, this epidemiological and demographic population shift is starting to have a major impact on health care systems.…”
Section: Impacts Of Frailty On Health Care Systemsmentioning
confidence: 99%
“…56 Multiple studies using cohorts of community-dwelling older adults have showed that the health care costs of frail individuals are sometimes several-fold higher than those of non-frail counterparts. [57][58][59][60][61] Older adults form the main users of medical and social care services, 62 and the majority of health care costs are incurred by them. In the context of ongoing population aging, with an unprecedented growing number and proportion of older adults, this epidemiological and demographic population shift is starting to have a major impact on health care systems.…”
Section: Impacts Of Frailty On Health Care Systemsmentioning
confidence: 99%
“…45 Frailty, in turn, is associated with higher total and outpatient healthcare costs and higher rates of hospitalization and SNF stays. 19 Our findings suggest that clinical attention to older adults with even mild, and not just moderate to severe, depressive symptoms may be warranted. Total healthcare costs are also an indicator of healthcare and illness burden among older individuals, and hence our data suggest that pharmacologic and/or psychotherapeutic interventions to address even mild depressive symptoms may be appropriate for some patients.…”
Section: Discussionmentioning
confidence: 73%
“…Two studies of individuals aged 65 years and older have shown that positive affect reduces the risk of incident frailty; in the SOF Caregiver study, this association remained significant after adjustment for age, comorbid medical conditions, and functional limitations . Frailty, in turn, is associated with higher total and outpatient healthcare costs and higher rates of hospitalization and SNF stays …”
Section: Discussionmentioning
confidence: 97%
“…10,11 We used a gamma distribution with a log link given our right-skewed cost distribution and a previous study using similar models. 12 The correlation structure was assumed to be exchangeable for repeated observations. Once the GEE model was fitted to our data, we extracted the marginal percent difference in costs due to frailty from the beta estimate for frail and nonfrail patients.…”
Section: Resultsmentioning
confidence: 99%